High Unemployment Records of Graduated Students in the Development of Urban Agriculture in the Gaza Strip - Al-Najar, Husam; Khalil, Hadi; Rahayu, Yuni Sri (Universitas Pendidikan Indonesia, 2019)
Urban agriculture plays a significant role in national development by contributing towards food security, job creation, and income generation. This study aims to assess the effect of unemployment records in graduated students in the recovery of the agricultural sector and the input to food security. A combination of both quantitative and qualitative research methods was employed in this study. In the quantitative design, 129 randomly selected urban farmers, completed the self-administered close-ended questionnaires, whereas the statistical analysis presents the socio-demographic, economic, and other aspects of the households. Based on the study result, around 2500 students graduated annually from 29 high educational institutes in Gaza Strip. The unemployment rate is around 41%, therefore the graduated students found that urban agriculture is contributing to create more jobs opportunities and improving household income. The analysis showed that 18% of the urban farmers are illiterate, 31% passed primary education, 25% passed secondary education, and 26% are holding university degrees in different fields. It is highly recommend to include urban agriculture in the future plans of the ministry of labours, ministry of agriculture, and all relevant institutions to overcome the high unemployment records and to alleviate poverty in Gaza.